Psychological Empowerment and Its Relationship with Organizational Commitment and Work Engagement Among Private Insurance Employees in Riyadh - Alotaibi, Saad (The Arab Journal of Administration, 2018)
The present study aims to investigate psychological empowerment and its relation to organizational commitment and work engagement, and its has sought to examine the role of psychological empowerment in predicting Organizational commitment and work engagement among private insurance employees in Riyadh, and to identify the contribution of psychological empowerment in predicting organizational commitment and work engagement. The study was carried out on a sample of (221) employees. The study tools included: psychological empowerment scale (Spreitzer, 1995), organizational commitment scale (Meyer et al., 1993), and work engagement scale (Schaufeli et al., 2006). The results showed a positive correlation between psychological empowerment and both of organizational commitment and work engagement, and psychological empowerment was a significant predictor of both organizational commitment and work engagement. Further analysis showed that all the dimensions of psychological empowerment, other than impact are predictor of both organizational commitment and work engagement.